Isolation and characterization of lactic acid bacteria with probiotic potential from traditional fermented special Kurdish cheese (Zhazhi) in Kurdistan Region, Iraq: Characterization of lactic acid bacteria with probiotic potential - Othman, Media Azeez; Karim, Abdulkarim Yasin (Cellular and Molecular Biology, 2023)
Zhazhi cheese is a unique farmhouse traditional fermented dairy of the Kurdistan Region in Iraq for its desired aroma and flavor. Undoubtedly, the lactic acid bacteria (LAB) are the critical factors in developing the aroma, flavor, and texture of Zhazhi cheese but it has not been studied or characterised. LAB has many important nutritional benefits, including increasing the nutritional value of food. Therefore, this research was performed to isolate and identify the potential probiotic LAB from traditional homemade Kurdish cheese. Then, the identified strains were tested to determine their probiotics traits, which include acid resistance, bile-salt tolerance, haemolytic, DNase, hydrophobic, autoaggregation, antimicrobial and antibiotic activities. The isolated five LAB strains comprised Lactobacillus casei, Lactobacillus rhamnosus, Enterococcus faecium, Pediococcus pentocaseus and Lactobacillus helvaticum were recognized as promising and the most potential probiotics for further applications. This is the first report on the direct selection of potentially probiotic LAB from Kurdish special cheese (Zhazhi).